Productive ground : 21st century design strategies for Fairmont Park - Martell, Natalie (Kansas State University, 2013)
As urban populations continue to grow, parks will become a critical component to creating and sustaining healthy cities. A review of literature related to landscape performance and 21st century parks reveals a paradigm shift in the ways we engage our built landscapes. No longer is it environmentally or fiscally responsible to implement and maintain resource consumptive city parks that are exclusively concerned with fulfilling social needs. To create environmentally, socially, and economically beneficial spaces, 21st century parks must include design elements and best management practices that ensure long-term sustainability. In Manhattan, Kansas, most of the city’s parks are recreation centric and primarily focused on fulfilling social needs. However, Fairmont Park has yet to be fully realized, and therefore presents the city an opportunity to implement its first sustainable park. Using the Sustainable Sites Initiative’s 2009 Guidelines and Performance Benchmarks as a guide, a series of sustainability evaluations were conducted on Fairmont Park’s existing conditions in order to reveal its current level of sustainability. To understand how the park was originally envisioned to perform, the same analysis was conducted on Fairmont Park’s 1998 Master Plan. Findings from this process revealed an opportunity to update the park’s current master plan, in order to achieve enhanced environmental, social, and economic benefits. Guided by 21st century park design, implementation, and management strategies, the redesign of Fairmont Park will not only help Riley County fulfill its goal of becoming a State leader in sustainable design, but it will provide the Manhattan community with a state-of-the-art productive park, which promotes environmental education and stewardship, physical activity, local food production and composting, and stormwater management practices.
Keywords: 21st century parks; Productive public space; Sustainable design; Landscape performance benefits; Park design; Landscape Architecture (0390)